PENGARUH OPERATING EFFICIENCY RATIO (OER) DAN NON PERFORMING FINANCING (NPF) TERHADAP PROFITABILITA PADA BANK UMUM SYARIAH PERIODE 2014-2020 - Nurlaela, Eel; Ponirah, Ade (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2022)
A company, especially in Islamic Commercial Banks, is inseparable from financing risks and the level of efficiency of bank performance in making a profit. As for the indicator of the success of the company making a profit is profitability. The data in this article is secondary data taken from the financial statements of Bank Umum Syairah for the 2014-2020 period, and is supported by literature and documentation research. Based on the results of the research, it was concluded that the OER variable has no effect on the profitability of ROA. Meanwhile, the NPF variable has a significant negative effect on roa profitability. Based on the results of the F test, simultaneously the OER and NPF variables have a significant effect on the profitability of ROA in Islamic Commercial Banks. This means that both variables can explain and affect the profitability of ROA by 45.27% and the remaining 54.73% is influenced by other variables that are not studied.Keywords : Operating Efficiency Ratio, Non Performing Financing, Profitabilitas